IMPLEMENTATION OF MANAGEMENT INFORMATION SYSTEMS IN THE INTEGRATED ISLAMIC BASIC SCHOOL (SD IT) AL IHYA KALIREJO BASED ON WEBSITE - Gusliana, Evi; Alwi, Habib; Khumaidi, Ahmad (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2020)
Information is one of the things that is needed in an organization or an agency. Information is also a need for management for an educational institution management. The school's website-based information system is a form of electronic media publication that can be used as a weapon for schools that want to show their identity to the wider community, as well as information media for outsiders who want to know completely the ins and outs of school. On the other hand, the website can also be used as a promotional medium for schools to attract prospective students during the new school year. The results of this study are to determine what efforts were made to implement a Website-Based Management Information System at SDIT Al Ihya Kalirejo. Knowing whether the application of a website-based Management Information System on SDIT Al Ihya Kalirejo is appropriate and knowing the factors that hinder the creation of a website-based Management Information System at SDIT Al Ihya Kalirejo. The division of labor in publications has become wider and the existence of this website-based management information system can be expected to be more efficient in cost, because by using this system the dissemination of information is easier and has a wider reach